Global transcriptome analysis of grapevine ( Vitis vinifera L.) leaves under salt stress reveals differential response at early and late stages of stress in table grape cv. Thompson Seedless - Upadhyay, Anuradha; Gaonkar, Tulsi; Upadhyay, Ajay Kumar; Jogaiah, Satisha; Shinde, Manisha P.; Kadoo, Narendra; Gupta, Vidya Shrikant (Plant Physiology and Biochemistry, 2018)
Among the different abiotic stresses, salt stress has a significant effect on the growth and yield of grapevine (Vitis vinifera L.). In this study, we employed RNA sequence based transcriptome analysis to study salinity stress response in grape variety Thompson Seedless. Salt stress adversely affected the growth related and physiological parameters and the effect on physiological parameters was significant within 10 days of stress imposition. A total of 343 genes were differentially expressed in response to salt stress. Among the differentially expressed genes (DEGs) only 42 genes were common at early and late stages of stress. The gene enrichment analysis revealed that GO terms related to transcription factors were over-represented. Among the DEGs, 52 were transcription factors belonging to WRKY, EREB, MYB, NAC and bHLH families. Salt stress significantly affected several pathways like metabolic pathways, biosynthesis of secondary metabolites, membrane transport development related pathways etc. 343 DEGs were distributed on all the 19 chromosomes, however clustered regions of DEGs were present on chromosomes 2, 5, 6 and 12 suggesting probable QTLs for imparting tolerance to salt and other abiotic stresses. Real-time PCR of selected genes in control and treated samples of grafted and own root vines demonstrated that rootstock influenced expression of salt stress responsive genes. Microsatellite regions were identified in ten selected salt responsive genes and highly polymorphic markers were identified using fifteen grape genotypes. This information will be useful for the identification of key genes involved in salt stress tolerance in grape. The identified DEGs could also be useful for genome wide analysis for the identification of polymorphic markers for their subsequent use in molecular breeding for developing salt tolerant grape genotypes.